Understanding HR attributions and creativity of SMEs employees in Colombia: a qualitative study - Lisseth Gutierrez-Gonzalez; Ernesto Monroy; Melissa Johnson Morgan; Retha Wiesner (Journal of Innovation and Entrepreneurship)
Abstract The purpose of this study is to understand employees’ attributions of human resource management (HRM) practices and how these attributions confluence with employees’ creativity. We propose the concept of human resource attribution (HR attribution) as a construct that can aid in understanding employees' creativity. This research studies how human resource (HR) attributions play a part in the creativity of employees in small- and medium-sized enterprises (SMEs) in Colombia's Atlántico Region. Semi-structured interviews were conducted with 12 SME employees. Our results were analyzed with reflexive thematic analysis. Generated themes enclosed individual factors (the HR attribution participants made, and the employees’ level of organizational commitment) and organizational factors (managerial practices). The results indicate that a key construct of employees’ creativity is their interpretation of why HRM practices are implemented. This suggests that the actual HRM practices are not always the elements that matter for employees’ creativity in all contexts. Furthermore, other individual and social constructs were found to be relevant to Colombian employees’ creativity. Future studies should quantitatively test the impact of HR attributions on SME employees’ creativity.